Gastrointestinal stromal tumor of the rectum: results of surgical and multimodality therapy in the era of imatinib - Jakob, Jens; Ronellenfitsch, Ulrich; Hohenberger, Peter (Annals of surgical oncology, 2013)
Background: The rectum is a rare site of gastrointestinal stromal tumor (GIST), and factors determining long-term outcome remain unclear. In a population study, we assessed the outcome of rectal GIST patients treated at two referral centers.MethodsA total of 39 patients diagnosed with rectal GIST between January 2002 and December 2010 were identified in prospective databases. Tumor and patient characteristics, treatment details, and outcome were evaluated. Median follow-up was 41 (3-110) months.ResultsA male predominance was noticed (M/F = 29/10). Median age was 53 years (range, 32-80 years). The cohort included, of 39 patients, 12 low-risk, 26 high-risk, and 1 with M1 disease. Of 38 patients with nonmetastatic disease, 36 underwent surgery as transabdominal (15 of 36) or local (21 of 36) resection. There were 21 patients who received preoperative and/or postoperative imatinib treatment. Patients with preoperative imatinib (16 of 36) had a significantly higher rate of R0 resections (p = .02). Five patients developed local recurrences. All of them had undergone local tumor excision with positive margins and without perioperative imatinib. Also, five patients suffered from distant metastases. All belonged to the high-risk group and underwent tumor surgery (3 R0, 2 R1) without receiving perioperative imatinib. A total of three patients died of disease. Perioperative imatinib was associated with improved local disease-free, disease-free, and overall survival (p < .01, p < .01, and p = .03, respectively). Local disease-free survival was significantly improved by negative resection margins (p < .01).ConclusionsComplete resection is recommended to achieve local disease control. Preoperative imatinib was associated with improved surgical margins. Perioperative imatinib was associated with improved local disease-free, disease-free, and overall survival.